Loss of Pulmonary Vascular Volume as a Predictor of Right Ventricular Dysfunction and Mortality in Acute Pulmonary Embolism. (21st September 2021) - Minhas, Jasleen; Nardelli, Pietro; Hassan, Syed Moin; Al-Naamani, Nadine; Harder, Eileen; Ash, Samuel; Sánchez-Ferrero, Gonzalo Vegas; Mason, Stefanie; Hunsaker, Andetta R.; Piazza, Gregory; Goldhaber, Samuel Z.; Waxman, Aaron B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In acute pulmonary embolism, chest computed tomography angiography derived metrics, such as the right ventricle (RV): left ventricle ratio are routinely used for risk stratification. Paucity of intraparenchymal blood vessels has previously been described, but their association with clinical biomarkers and outcomes has not been studied. We sought to determine if small vascular volumes measured on computed tomography scans were associated with an abnormal RV on echocardiography and mortality. We hypothesized that decreased small venous volume would be associated with greater RV dysfunction and increased mortality. Methods: A retrospective cohort of patients with intermediate risk pulmonary embolism admitted to Brigham and Women's Hospital between 2009 and 2017 was assembled, and clinical and radiographic data were obtained. We performed 3-dimensional reconstructions of vasculature to assess intraparenchymal vascular volumes. Statistical analyses were performed using multivariable regression and cox proportional hazards models, adjusting for age, sex, lung volume, and small arterial volume. Results: Seven hundred twenty-two subjects were identified of whom 573 had documented echocardiography. A 50% reduction in small venous volume was associated with an increased risk of RV dilation (relative risk: 1.38 [95% CI, 1.18–1.63], P <0.001), RV dysfunction (relative risk: 1.62 [95% CI, 1.36–1.95], P <0.001), and RV strain (relative risk: 1.67 [95% CI, 1.37–2.04], P <0.001); increased cardiac biomarkers, and higher 30-day and 90-day mortality (hazard ratio: 2.50 [95% CI, 1.33–4.67], P =0.004 and hazard ratio: 1.84 [95% CI, 1.11–3.04], P =0.019, respectively). Conclusions: Loss of small venous volume quantified from computed tomography angiography is associated with increased risk of abnormal RV on echocardiography, abnormal cardiac biomarkers, and higher risk of 30- and 90-day mortality. Small venous volume may be a useful marker for assessing disease severity in acute pulmonary embolism.